2020
DOI: 10.3846/btp.2020.11551
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Women Behavior Towards the Acceptance of Industrial Small Business

Abstract: The aim of this research was to canvass Saudi women’s opinions about behavioral beliefs, i.e., attitudes, subjective norms and perceived behavioral control on their behavioral intention and hence adopting the small business initiative. Following the descriptive method, adopting the planned behavior theory PBT, a questionnaire consisted of 15 items was adapted to measure the variables of the research, i.e., three predictors, which are attitudes toward the behavior, subjective norms and perceived behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…It was acknowledged that perceived behavioral control (PBC) is a key predictor of individuals' BIs (Baker and White, 2010). Previous related works in Saudi Arabia such as Almohaimmeed et al (2020) study revealed significant and positive effects of the PBC on both BI and the behavior of Saudi women to accept small business ventures as well as women's BI mediated the effect of their PBC on their actual behavior. Therefore, the following hypotheses were assumed: H5: There is a significant effect of PBC on WEB.…”
Section: Pbc Bi and Webmentioning
confidence: 96%
See 4 more Smart Citations
“…It was acknowledged that perceived behavioral control (PBC) is a key predictor of individuals' BIs (Baker and White, 2010). Previous related works in Saudi Arabia such as Almohaimmeed et al (2020) study revealed significant and positive effects of the PBC on both BI and the behavior of Saudi women to accept small business ventures as well as women's BI mediated the effect of their PBC on their actual behavior. Therefore, the following hypotheses were assumed: H5: There is a significant effect of PBC on WEB.…”
Section: Pbc Bi and Webmentioning
confidence: 96%
“…Consequently, attitudes toward a given behavior increase individuals' involvement in EBs (Joensuu-Salo et al, 2021). In a recent study conducted by Almohaimmeed et al (2020) on Saudi women's behavior towards the acceptance of industrial small businesses, it was found that their attitudes towards the behavior had a significant effect on their BI, which in sequence influenced their actual behavior to accept small business initiatives. To predict Saudi women's attitudes toward entrepreneurial small business, the following hypotheses were suggested: H1: There is a significant effect of ATB on WEB.…”
Section: Atb Bi and Webmentioning
confidence: 99%
See 3 more Smart Citations